Pengukuran waktu standar proses kerja mesin bandsaw dan cross cut untuk perencanaan dan evaluasi pemenuhan pesanan - F Edwin Wiranata; Claudia Fremtama Br Simarmata; Lenny Halim (Jurnal Teknik Industri dan Manajemen Rekayasa, 2023)
The furniture industry is continuously innovating to produce the best products, with buyers' preferences related to function, quality, and design. Companies need to optimize machine cycle times and reformulate production time durations to increase productivity s. Lead time needs to be optimized to anticipate order fulfillment until the transaction is completed on time. Standard time is critical to setting production targets, budgets, product cost estimates, machine requirements, and determining standard operator wages in measuring productivity efficiency. Companies in the garden furniture sector need to calculate standard time in their production processes, particularly in the RST (Raw Saw Tinder) processing stage, to achieve timely production targets and avoid potential losses. Productivity analysis in the production area of the RST processing stage is carried out by calculating the standard time of the bandsaw and cross-cut or radial arm saw machines. The research is conducted through the motion study measurement, uniformity and sufficiency testing of data, and normal and standard time calculations to determine the required duration for each production stage. The time study measurement results and standard time calculations for the 18 work elements show that the standard time in the RST processing stage is 4.92 minutes or equivalent to 12 units/hour, which means the company can ideally produce 88 units of products per day.